URGENCY OF CHANGE AGENTS IN TRANSFORMATION OF EDUCATIONAL INSTITUTIONS AT PESANTREN TEBUIRENG JOMBANG - Subhi, Imam; Priansyah, Deni; Rahman, Rahman; Risdianto, Risdianto; Hadi, Supian (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to explore data about the urgency of change agents in achieving transformation at the Tebuireng Islamic Boarding School, especially at leadership era of KH Salahudin Wahid, according to several research results, stated comprehensive changes in various aspects of Islamic boarding schools. To obtain comprehensive data, this research used a case study approach, with data collection methods through literature review, documentation study, observation, and discussion groups. The conclusion of this study states that the changes that occur at the Tebuireng Islamic Boarding School are carried out by three important elements, namely primary or key agents, who act as figures of inspiration, authority, motivation, character and independence to make changes, while secondary agents are figures who help providing an insight, encouraging, communicating and achieving change; whereas the consultants are external parties, either personal or institutional, who is asked for assistance and strengthened through a memorandum of understanding or MOU to assist in the change process at the Tebuireng Islamic Boarding School.